Negative maxillary transverse discrepancy and cephalometric lateral differences according to the width of upper arch - Michele García Menéndez; Lauren Perdomo Gutiérrez; Diana Valdés Massó (Editorial Ciencias Médicas, 2021)
Introduction: Negative maxillary transverse discrepancy is not exclusive to narrow upper arch. The transverse discrepancy due to maxillary deficiency is well described, but this is not the case when the maxilla displays adequate dimensions and the origin of the problem is an excess of mandibular width. Objective: To describe the cephalometric characteristics of negative maxillary transverse discrepancy present in narrow upper arches with those of normal or increased width. Methods: An observational and cross-sectional study was carried out in records of patients with negative maxillary transverse discrepancy. The cases referred to the maxillofacial surgery department at Hospital Clínico Quirúrgico "Hermanos Ameijeiras" between January 2016 and January 2020 were selected. The initial study models were measured and two groups were formed: those with a distance between central fossae of 16 to 26, less than 47 mm and the other with equal or greater values. Lateral cephalometric analysis of Ricketts, McNamara, Björk & Jarabak, Burstone and soft profile were performed on the initial teleradiographs. Using the Mann Whitney U test of independent samples, measurements with statistically significant differences between both groups were selected. (p <0.05). Results: Significant differences were found regarding the cranial-mandibular relationship, mandibular anatomy, maxillo-mandibular relationship and occlusal relationship. The most important differences observed in each group were respectively: S-Ar / Ar-Go ratio (p = 0.033), mandibular body length (p = 0.01), mandibular-maxillary difference (p = 0.003) and overjet (p = 0.043). Conclusions: In the studied patients, negative maxillary transverse discrepancy has the same probability of presenting a wide or in norm upper arch, as well as a narrow arch. In the first case, it is more likely to find jaws with increased body length, a skeletal class III pattern and a concave profile; in the second case, the tendency is to present small jaws with increased articular angle and dental overjet.